Review on Training and Development in Human Management - Abang Mohd. Razif Abang Muis; Abdul Hair Beddu Asis; Syamsul Azizul Marinsah; Mohd Nur Hidayat Hasbollah Hajimin; Musmuliadi Kamaruding; Mohd. Taqwudin Mohd. Yazid (Human Resource Management Academic Research Society (HRMARS), 2021)
The purpose of this paper is to help in term of providing a better understanding on training and development in human management amongst the researchers on this field. Training and development should be the important aspect increase the workers potential in the organisations. The lack of training and development will give a negative impact in the organisations such as inefficiency, deviation, misconduct, and bribery act freely amongst workers. The aim of this study is realized by profiling existing literature to understand the determinants of training and development in human management, research trends, theories, and future research opportunities. A comprehensive search was initiated on Google Scholar, Scopus, Emerald Insight, JSTOR, and ProQuest. Final inclusion criteria were systematic reviews on training and development in human management. Articles were screened in three components by the title, abstract and full text. Data was abstracted by identifying general information, outcome, conclusions, and recommendations of each reviewed paper. After cautiously and carefully examining the extant literature and by utilizing these relevant academic-based research databases, a total of 100 papers published in peer-reviewed journals over the last decade were reviewed and analysed using well-established systematic review methodology. In the initial search, 158 potential reviews were identified. After removing same papers, 97 articles were excluded by screening the title or abstract. After a full text review of each article, 47 papers were included in the final synthesis. The adopted systematic review revealed that there are limited contributions in understanding training and development in human management. The review provides several venue for future research including training and development concepts, models, forms, contents, and evaluations aspect at different levels.